Characterization of Light Diffraction by a Digital Micromirror Device. Issue 1 (1st December 2022) - Pereira, C; Abreu, M; Cabral, A; Rebordão, J M
Abstract: A Digital Micromirror Device (DMD) is a technology developed by Texas Instruments, that consists in a two-dimensional array of micromirrors, which can be individually tilted between two positions. It has been used as a digital video and image processing solution, commonly found in Digital Light Processing (DLP) video projectors. Over the years, DMDs have become popular in different fields: industrial, automotive, medical, government and home user solutions. In the astronomy field, it has been also considered in on-ground space instrumentation and it has been proposed for the development of some astrophysical space instruments. In order to evaluate the actual impact of such device in the instrument optical design, it is important to know how the light behaves when it interacts with a DMD, namely in what regards to the diffraction process when a light beam is reflected by a periodic array of micromirrors. In this study we describe how we simulate the diffraction patterns produced by a periodic array of micromirrors, for coherent and incoherent sources of light. The results from simulations are verified against laboratory experiments, described also in this study.